Capital budgeting : financial appraisal of investment projects - Dayanada, Don (Cambridge University Press, 2002)
Explains the financial appraisal of capital budgeting projects. Develops basic concepts, principles and techniques and applies them in complex real-world situations such as forestry, property and international investments. All computations in the book are extensively supported by Excel workbooks on the Web, each chapter contains questions for teachers and students.